Pengembangan E-Modul IPA Berbasis Google Slide Dengan Tema Global Warming Untuk Menumbuhkan Minat Belajar Siswa SMP Kelas VII - Ami Amimah; Suroso Mukti Leksono; Annisa Novianti Taufik (PendIPA Journal of Science Education, 2023)
Interest in learning is a psychological aspect that influences every student in learning because the interest that students have will give rise to feelings of liking, interest, attention and involvement of students in learning activities without any compulsion. Based on the results of interviews at one of the schools in Cilegon City, it found that student's interest in learning was still relatively low because the teaching materials used by teachers were still relatively less varied and less interesting. This can be overcome by developing teaching materials in the form of science e-modules based on Google Slides. This research aimed to identify the level of validity of developing a Google Slides-based science e-module with the theme of global warming to foster students' interest in learning. The research method used was Research and Development (R&D) according to Borg and Gall which is modified according to the needs of researchers and limited to the stages of design validation to product revision. The instrument used in this research was an expert validation questionnaire sheet which has been tested by instrument experts to determine the level of validity of the e-module being developed. Data was analyzed quantitatively and qualitatively. The results of this research were based on the percentage of scores from experts, namely 91.1% in the "Very Valid" category. This shows that the Google Slides-based science e-module with the theme of global warming is very valid for fostering interest in learning for class VII middle school students.